Factor analysis of prices for key raw materials for manufacturing building materials and products in Ukraine - Skrypnyk, О. (Ways to Improve Construction Efficiency, 2019)
In the article the processes of effective pricing for maximizing profits at the enterprises of the building materials industry are investigated. The main factors of pricing are determined and their correlation analysis is carried out in order to find an effective mechanism for pricing policy formation at the enterprises under study. The linear regression equations for forecasting prices for key raw materials for the production of building materials are determined.